Comparative analysis of Facebook and communication activities of the mountain hotels in Stara planina, Kopaonik and Zlatibor - Živković, Radmila; Njeguš, Angelina; Zlatanović, Marija; Gajić, Jelena; Brdar, Ivana (The European Journal of Applied Economics, 2015)
Communication strategies with the consumers of tourism products and services have significantly transformed in recent years with the advent of social media and online information. According to numerous authors, social media represent a hybrid form of traditional integrated marketing communications with the increased effect of WOM (word of mouth) communication, which enables the exchange of information between users/consumers. The transparency of social media provides the hoteliers with necessary feedback and opens up new communication channels. Modern consumers possess greater knowledge and higher expectations than before. The purpose of the research conducted on a sample of mountain hotels in Serbia using web metrics was to determine guest perception and satisfaction with the hotels at the most popular Serbian mountain destinations. The results show that social networks can be used successfully by service providers to improve the understanding of guests’ needs, as well as to enhance business performance and revenue. By maintaining long-term relationships with guests, hoteliers can build stronger and more enduring connections that will result in new purchases and more efficient WOM (word of mouth).